ASSESSMENT OF PREGNANCY OUTCOME IN PRIMIGRAVIDA: COMPARISON BETWEEN BOOKED AND UN-BOOKED PATIENTS - Danish, Nargis; Fawad, Aneesa; Abbasi, Nasreen (Journal of Ayub Medical College Abbottabad, 2010)
Background: Primigravida (PG), defined as a woman who conceives for the first time, is in a high-risk group. Objective of this study was to evaluate the pregnancy outcome in booked and un-booked primigravida. Methods: This was a hospital based comparative study conducted in Women and Children Hospital Abbottabad from May 1998 to November 1999. A total of 322 patients were included in the study. Inclusion criteria was all primigravida, both booked as well as un-booked patients. Evaluation was done by taking detailed history, clinical examination and relevant investigations. Antenatal, intrapartum and postnatal complications were noted in the mothers. Perinatal morbidity and mortality was assessed in both the groups. Results: Out of 322 cases, 52 patients were booked and 270 patients were un-booked. Majority of un-booked patients belonged to the rural areas and were from lower socioeconomic group, between the age group of 15-35 years. The rate of instrumental deliveries was high (87.5%) in un-booked patients as compared to booked patients (12.5%). Caesarean section rate in un-booked patients was higher (76.5%) as compared to booked patients (23.5%). Twenty-three (20%) patients of un-booked group presented in emergency mainly with obstructed labour. Twenty-two (19.8%) patients had pregnancy induced hypertension, while foetuses of 48 (43.2%) patients developed foetal distress. Antipartum haemorrhage was present in 12 (10.8%) patients, while prolonged labour with foetal distress was noted in 26 (23.4%) patients in unbooked group. Postpartum haemorrhage and puerperal pyrexia was more common in un-booked patients (7.7% and 18.6% respectively). Perinatal mortality was high in un-booked patients (19.5%) as compared to booked patients. Conclusion: Primigravida are high-risk patients. Comprehensive antenatal care should be provided in this group of patients to have better maternal and foetal outcome. Keywords: Primigravida, Pregnancy, Outcome, Complications, Women, Antenatal, Maternal, foetal